1991
DOI: 10.1152/ajpcell.1991.260.4.c805
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnic acidosis and increased H2PO4- concentration do not decrease force in cat skeletal muscle

Abstract: Peak tetanic tension was measured during acidosis resulting from either hypercapnia or repetitive tetanic stimulation in isolated, arterially perfused cat biceps brachii (predominantly fast twitch) or soleus (slow twitch) muscles. Phosphocreatine (PCr), Pi, intracellular pH (pHi), and extracellular pH (pHo) were monitored by 31P-nuclear magnetic resonance spectroscopy. During repetitive stimulation under normocapnic conditions (5% CO2, pHo 7.4) Pi increased, pHi decreased from 7.1 to 6.3, and there were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
31
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 31 publications
8
31
0
Order By: Relevance
“…Ranatunga (365) found that twitch and tetanic force in rat EDL bundles at 30 -35°C were not decreased at acid pH i (likely ϳ6.5), but actually potentiated. In cat muscle in vivo at 37°C, decreasing muscle pH i to 6.3 by hypercapnia reduced maximum tetanic force by only ϳ5-10% in soleus and biceps brachii muscles (2). In intact single fibers from mouse at 32°C, decreasing pH i from 7.17 to 6.67 caused only ϳ10% reduction in maximum tetanic force and no significant slowing of the maximum velocity of shortening (472).…”
Section: Ph I and Muscle Fatiguementioning
confidence: 93%
“…Ranatunga (365) found that twitch and tetanic force in rat EDL bundles at 30 -35°C were not decreased at acid pH i (likely ϳ6.5), but actually potentiated. In cat muscle in vivo at 37°C, decreasing muscle pH i to 6.3 by hypercapnia reduced maximum tetanic force by only ϳ5-10% in soleus and biceps brachii muscles (2). In intact single fibers from mouse at 32°C, decreasing pH i from 7.17 to 6.67 caused only ϳ10% reduction in maximum tetanic force and no significant slowing of the maximum velocity of shortening (472).…”
Section: Ph I and Muscle Fatiguementioning
confidence: 93%
“…Vol. 61,2004 Review Article 1003 Figure 1. Typical series of 31 P MR spectra recorded with a time resolution of 2 s at end of exercise (first spectrum, bottom) and during the following recovery period.…”
Section: Contribution Of 31 P Mrs To the Study Of Peripheral Fatiguementioning
confidence: 99%
“…This phenomenon would decrease the proportion of force-producing cross-bridges, leading to a decline in force production. Attempts to show the inhibitory effect of P i on force under physiological conditions have mainly been performed using 31 P MRS [11,61,69,[76][77][78] and focused on P i and H 2 PO 4 -time-dependent changes, one the one hand, and force reduction, on the other hand [75]. A strong correlation has been demonstrated between H 2 PO 4 -accumulation and force reduction in human muscle during different types of experimental protocols including sustained or repeated contractions with maximal or submaximal intensities [69,76,77].…”
Section: P I Accumulation: a Causative Factor Of Fatigue?mentioning
confidence: 99%
“…The decline in force has been demonstrated to strongly correlate with an increase in muscle P i concentration (7,44,50). Although the strength of the correlation varies (1), in the later stages of fatigue, when maximal isometric force is depressed by Ͼ70%, the intracellular P i concentration can exceed 30 mM compared with the 1-5 mM level in resting fibers (44). These observations suggest that P i may play a causative role in fatigue.…”
mentioning
confidence: 99%